28. CLINICAL CHARACTERISTICS AND RESULTS OF TREATMENT OF HAND-FOOT-MOUTH DISEASE IN CHILDREN AT NGHE AN OBSTETRICS AND PEDIATRICS HOSPITAL IN 2023-2024 (Vietnam Journal of Community Medicine, 2025)
Objective: The study aimed to evaluate the clinical characteristics and treatment outcomes of hand, foot and mouth disease.Subjects and methods: Retrospective, prospective, cross-sectional study of 469 children treated at Nghe An Obstetrics and Pediatrics Hospital.Results: The disease affects both sexes, in which men account for more than women with a male/female ratio = 1.8/1. The age group with the highest incidence of the disease is from 12 months to 36 months, accounting for 59.1%. The number of sick days a child has before being hospitalized is mainly less than 3 days, accounting for 94.7%. Initial symptoms of the disease are mainly fever (98.9%), rash (96.6%), and ulcers. mouth (71.4%). Patients mainly suffer from both types of damage (erythema and blisters): 50.1%. The number of days of fever in hand, foot and mouth patients is mainly less than 3 days, accounting for 58.8%, the number of days of fever being more than 7 days is less than 1.1%. Most children have clinical grade 2a (98.7%), only 1.3% have grade 2b. Drugs used in the treatment of hand, foot and mouth disease are mainly sedatives (82.3%) and fever reducers (49.3%). Only 1.3% of children were prescribed IVIG. 99.6% of children were cured of the disease and no child had sequelae.Conclusions: Most children have stage 2a disease and most of them are completely cured.
Keywords: Hand; foot and mouth disease in children; clinical; treatment results